Cellulose Nanocrystals from Forest Residues as Reinforcing Agents for Composites: A Study from Macro- to Nano-Dimensions. (30th March 2016) - Moriana, Rosana; Vilaplana, Francisco; Ek, Monica
Highlights: Cellulose nanocrystals (CNCs) from three logging residues are successfully isolated. The isolation process from the residues is monitored from macro to nano-dimensions. All isolated CNCs show high aspect ratio, crystallinity and thermal stability. Pine needle CNCs have higher crystallinity and purity than branch and chips CNCs. Extracted CNCs show potential to be used as reinforcing agents in composites. Abstract: This study investigates for the first time the feasibility of extracting cellulose nanocrystals (CNCs) from softwood forestry logging residues (woody chips, branches and pine needles), with an obtained gravimetric yield of over 13%. Compared with the other residues, woody chips rendered a higher yield of bleached cellulosic fibers with higher hemicellulose, pectin and lignin content, longer diameter, and lower crystallinity and thermal stability. The isolation of CNCs from these bleached cellulosic fibers was verified by the removal of most of their amorphous components, the increase in the crystallinity index, and the nano-dimensions of the individual crystals. The differences in the physico-chemical properties of the fibers extracted from the three logging residues resulted in CNCs with specific physico-chemical properties. The potential of using the resulting CNCs as reinforcements in nanocomposites was discussed in terms of aspect ratio, crystallinity and thermal stability.